Fundamental changes of granular flow dynamics, deposition, and erosion processes at high slope angles: Insights from laboratory experiments. Issue 3 (13th March 2014) - Farin, Maxime; Mangeney, Anne; Roche, Olivier
<x xml:space="preserve">Abstract</x> Entrainment of underlying debris by geophysical flows can significantly increase the flow deposit extent. To study this phenomenon, analog laboratory experiments have been conducted on granular column collapse over an inclined channel with and without an erodible bed made of similar granular material. Results show that for slope angles below a critical value θc, between 10° and 16°, the run out distance rf depends only on the initial column height h0 and is unaffected by the presence of an erodible bed. On steeper slopes, the flow dynamics change fundamentally, with a slow propagation phase developing after flow front deceleration, significantly extending the flow duration. This phase has characteristics similar to those of steady uniform flows. Its duration increases with increasing slope angle, column volume, column inclination with respect to the slope and channel width, decreasing column aspect ratio (height over length), and in the presence of an erodible bed. It is independent, however, of the maximum front velocity. The increase in the duration of the slow propagation phase has a crucial effect on flow dynamics and deposition. Over a rigid bed, the development of this phase leads to run out distances rf that depend on both the initial column height h0 and length r0. Over an erodible bed, as the duration of the slow propagation phase increases, the duration of bed excavation increases, leading to a greater increase in the run out distance compared with that over a rigid bed (up to 50%). This effect is even more pronounced as bed compaction decreases.